2023
DOI: 10.1186/s12984-023-01239-z
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between muscle pathophysiology, body mass, walking speed and ankle foot orthosis stiffness on walking energy cost: a predictive simulation study

N. F. J. Waterval,
M. M. van der Krogt,
K. Veerkamp
et al.

Abstract: Background The stiffness of a dorsal leaf AFO that minimizes walking energy cost in people with plantarflexor weakness varies between individuals. Using predictive simulations, we studied the effects of plantarflexor weakness, passive plantarflexor stiffness, body mass, and walking speed on the optimal AFO stiffness for energy cost reduction. Methods We employed a planar, nine degrees-of-freedom musculoskeletal model, in which for validation maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…With suboptimal AFO settings, the out-of-plane compensation, such as trunk motions, are known to be more extreme ( Meyns et al, 2020 ), hence the sensitivity of the mCoT trend to AFO stiffness could be higher in reality than in our predictive gait simulations. However, most of the gait changes with AFO use on patients with plantar flexor weakness occur in the sagittal plane ( Waterval et al, 2019 ; Waterval et al, 2023 ). Additionally, Donelan et al showed that providing external lateral stabilization to subjects walking on a treadmill with their preferred step width reduced their metabolic cost only by 5.7% ( Donelan et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With suboptimal AFO settings, the out-of-plane compensation, such as trunk motions, are known to be more extreme ( Meyns et al, 2020 ), hence the sensitivity of the mCoT trend to AFO stiffness could be higher in reality than in our predictive gait simulations. However, most of the gait changes with AFO use on patients with plantar flexor weakness occur in the sagittal plane ( Waterval et al, 2019 ; Waterval et al, 2023 ). Additionally, Donelan et al showed that providing external lateral stabilization to subjects walking on a treadmill with their preferred step width reduced their metabolic cost only by 5.7% ( Donelan et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Donelan et al showed that providing external lateral stabilization to subjects walking on a treadmill with their preferred step width reduced their metabolic cost only by 5.7% ( Donelan et al, 2004 ). Consequently, as sagittal plane muscle actions contribute most of the total metabolic cost ( Donelan et al, 2004 ) and most of its adaptations to AFOs ( Waterval et al, 2019 ; Waterval et al, 2023 ), our goal to explain the convex relation between mCoT and AFO stiffness can be done with a planar model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation